Long-term stability of carbon dioxide electrolysis in a large-scale flat-tube solid oxide electrolysis cell based on double-sided air electrodes - Lu, Lianmei; Liu, Wu; Wang, Jianxin; Wang, Yudong; Xia, Changrong; Zhou, Xiao-Dong; Chen, Ming; Guan, Wanbing (Applied energy, 2020)
•CO2 electrolysis in a new solid oxide electrolysis cell was conducted.•47.4% conversion rate of CO2 was achieved at 1.305 V and −400 mA/cm2.•Energy conversation efficiency reached 91.4% at −400 mA/cm2 and 1.305 V.•1910 h of CO2 electrolysis has been operated under −300 mA/cm2. Solid oxide electrolysis cell is a highly promising technology for CO2 electrolysis and has attracted wide attention. But the durability is insufficient by known designed structure of solid oxide electrolysis cell due to structure damage. In this work, a new flat-tube solid oxide electrolysis cell (SOEC) based on double-sided air electrodes with mechanically-strong redox properties and larger active area was proposed and applied to electrolysis of CO2, and its electrochemical performance and long-term durability were investigated. The results showed that the charging current density reaches −600 mA/cm2 at 1.5 V and 750 °C under H2/CO2 atmosphere. The CO2 conversion rate achieves 47.4% with energy conversation efficiency of 91.4% at the electrolysis voltage of 1.305 V under the charging current density of −400 mA/cm2, corresponding to 210 mL/min of CO production rate. This new cell architecture for CO2 electrolysis was stable at the current density of −300 mA/cm2 for 1910 h at 750 °C with a degradation rate of 4.89%/kh. The new flat-tube solid oxide electrolysis cell is capable to conduct CO2 electrolysis with high efficiency and long-term stability.